The Impact of Physical Environmental Quality in Playgroups on the Health of Young Children - Marlini Marlini; Deby Utami Siska Ariani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Background: The health of early childhood is significantly influenced by the environment in which they grow and learn, including the physical environment of playgroups. An unhealthy environment can increase the risk of health problems such as respiratory infections, diarrhea, and skin disorders. This study aims to analyze the influence of the physical environment quality in playgroups on the health status of young children. Methods: This research employed a quantitative design with a descriptive correlational approach. A total of 32 children and their learning environments were selected using total sampling from KB Ar Rosyada, Lawang Wetan District, Banyuasin Regency. Data were collected through observations and interviews using physical environment assessment instruments and health status records of the children. Bivariate analysis was performed using the Spearman correlation test. Results: Most components of the physical environment were categorized as good, particularly ventilation (62.5%), cleanliness (65.6%), and sanitation (59.4%). A total of 62.5% of the children were found to be in good health without complaints. The analysis revealed a significant relationship between ventilation quality (p = 0.003), cleanliness (p = 0.002), and sanitation (p = 0.005) with the children’s health status. Lighting (p = 0.021) and temperature-humidity (p = 0.034) also showed significant associations, although with weaker correlations. Conclusion: Good physical environment quality has a significant influence on the health of early childhood. Improving and maintaining the physical environment of playgroups is crucial as a promotive and preventive strategy to enhance child health outcomes.